2015
DOI: 10.1590/s1517-838246320140403
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated vancomycin resistant <italic>Enterococcus faecium</italic> infections in the Mansoura University Hospitals intensive care units, Egypt

Abstract: Vancomycin resistant Enterococcus faecium (VREF) ia an emerging and challenging nosocomial pathogen. This study aimed to determine the prevalence, risk factors and clonal relationships between different VREF isolates in the intensive care units (ICUs) of the university hospitals in our geographic location. This prospective study was conducted from July, 2012 until September, 2013 on 781 patients who were admitted to the ICUs of the Mansoura University Hospitals (MUHs), and fulfilled the healthcare-associated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
6
25
0
Order By: Relevance
“…In our study, length of current hospitalization for ≥ 2 weeks was significantly important factor (P = 0.025). Our study finding is concordant with most previous studies from Egypt [ 28 ]. Longer hospital stays can indicate a greater chance of receiving antibiotics and also a longer exposure time to possible pathogen selection or transmission.…”
Section: Main Textsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, length of current hospitalization for ≥ 2 weeks was significantly important factor (P = 0.025). Our study finding is concordant with most previous studies from Egypt [ 28 ]. Longer hospital stays can indicate a greater chance of receiving antibiotics and also a longer exposure time to possible pathogen selection or transmission.…”
Section: Main Textsupporting
confidence: 94%
“…The current study showed that 22.7% of the isolates were resistant to vancomycin which is comparable with finding from Tabriz in Iran [ 29 ] and Mansoura in Egypt [ 28 ], but higher than the prevalence reported from Turkey, 1.55% [ 30 ]; 10% [ 31 ] and 16% [ 32 ] from Iran. But lower than the findings from Serbia, 54% [ 33 ]; Iran [ 34 ] and Nigeria, 42.9% [ 20 ] in clinical isolates from all age groups.…”
Section: Main Textsupporting
confidence: 85%
“…Regarding associated factors, the current study revealed that HIV patients who were exposed to antibiotics for more than two weeks previously were seven times more likely to be colonized with VRE as compared with HIV patients who never exposed to antibiotics previously [AOR = 7.35; 95% CI: (1.21-44.64); P-value = 0.030]. This result is in agreement with other studies conducted in Brazil (1), South Korea (43), Egypt (44), and Gondar and Ethiopia (2). The reason might be a prior exposure to antibiotics for a prolonged duration can cause VRE colonization due to the fact that the antibiotics exert selective pressure to Enterococci and alter the competing microbial ora in the GI tract allowing VRE to predominate as evidenced by other studies (7,34).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported the association of various risk factors for VRE colonization such as prolonged hospitalization, immunosuppression, younger age group, prolonged antibiotic consumption such as vancomycin, teicoplanin, amikacin, and ceftazidime, administration of antimicrobial therapy for the late onset of neonatal sepsis. [ 1 5 9 10 11 12 13 14 15 ] In this study, the consumption of vancomycin was the only risk factor significantly associated with the VRE colonization. In contrast, in a study from our center in adult patients admitted to MICU, we observed prior ceftriaxone administration to be a significant risk factor.…”
Section: Discussionmentioning
confidence: 62%
“…[ 8 ] The risk factors, namely, prolonged hospitalization, immunosuppression, low birth weight, younger age group, and prolonged antibiotic consumption of vancomycin, teicoplanin, amikacin, and ceftazidime were found to be associated with VRE colonization in pediatric and newborn ICUs and also in children's hospitals. [ 5 9 10 11 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%